Estrategia socioeducativa para prevenir y contrarrestar el bullying - Fauta Ramos, Silvia Liliana (2020)
The research is based on the need to improve the interpersonal relationships of students and prevent bullying as a particular form of school violence, for which it projects as a general objective: Develop a strategy socio-educational for the improvement of interpersonal relationships and bullying prevention. The research is based on the qualitative paradigm and uses methods and techniques useful for the purposes pursued such as: analysis and synthesis, modeling, inductive deductive, interview, case study, triangulation and the sociometric test is also used, which allowed the analysis epistemological and bullying diagnosis. The results of the case study allow to sustain that the elaborated socio-educational strategy constitutes a feasible and viable alternative for the improvement of interpersonal relationships and the prevention of bullying as a particular form of school violence.